The Comparative Study of Visual and Auditory Learning Style on Jigsaw Strategy in Students’ Reading Comprehension at Junior High School - Heppy Naibaho; Sondang Manik (Institut Agama Islam Negeri Palopo, 2023)
This study aimed to idenify (1) wether there was an effect of using Jigsaw Strategy on Students' reading Comprehension of visual and auditory Learning Style at SMP Negeri 3 Lintonghihuta. (2) whether there was different effect of using Jigsaw Strategy on Students' reading Comprehension of visual and auditory Learning Style at SMP Negeri 3 Lintonghihuta. The design of this study was mixed design quantitative comparation with quasi - experimental research that aimed to determine whether the relationship between the experimental group and comparison group in reading comprehension, the experimental group is the group that received the treatment. One class from the population was taken as samples by using a purposive-sampling technique. There were 32 students were taken as populations from class IX – 1. The class will be taught by Jigsaw strategy to know the reading comprehension achievement then compared between the auditory and visual learning style. The results of this study were (1) there was different post-test score between auditory and visual class where the visual class had higher score (71,25) than the auditory class (67,00) after being taught using jigsaw strategy. The result of the paired sample t-test showed that the values of sig (2-taieled) was 0,000 < 0,050 which means that there was significant different between the Pre-test and Post-test and it can be concluded that there was mean difference between the pre-test and the post-test of reading comprehension score of visual and auditory learning style after taught using jigsaw strategy.(2) Based on the ANCOVA test it was found that the value of level of significance of learning style was 0.120 and the value of level of Jigsaw strategy significance level was 0,162. It can be said that there was no significance effect of jigsaw strategy on students’ reading comprehension of auditory and visual and auditory Learning Style at SMP Negeri 3 Lintonghihuta.